Establishing and Maintaining Program Coherence in a Cohort-Based Graduate Program - Lamb, Lisa Clement; Jacobs, Victoria R. (The Teacher Educator, 2009)
One characteristic of master's programs that has received little attention in the literature is the opportunity that cohorts allow for creating intellectually coherent programs rather than a collection of independent courses. We thus describe how the faculty who taught in a cohort for students earning a master of arts degree in K–8 mathematics education created a coherent program by (a) identifying unifying themes that cut across courses, (b) building on ideas from one semester to the next, and (c) linking assignments for courses taught within the same semester. We share examples of each of these three features of our cohort model, as well as students' reflections on the program. The reflections support the notion that these features were both transparent and valuable to students.